Low brown adipose tissue activity in endurance-trained compared with lean sedentary men - Vosselman, M J; Hoeks, J; Brans, B; Pallubinsky, H; Nascimento, E B M; van der Lans, A A J J; Broeders, E P M; Mottaghy, F M; Schrauwen, P; van Marken Lichtenbelt, W D (International Journal of Obesity, 2015)
Background/objectives: It has now been unequivocally demonstrated that humans possess functional brown adipose tissue (BAT) and that human BAT can be recruited upon chronic cold stimulation. Recruitment of BAT has been postulated as a potential strategy to counteract the current global obesity epidemic. Recently, it was shown in rodents that endurance exercise training could stimulate the recruitment of brown-like adipocytes within white adipose tissue (WAT) via exercise-induced myokines such as irisin (the cleaved circulating product of the type 1 membrane protein FNDC5) and interleukin-6 (IL-6). Our objective was to test whether endurance-trained athletes had increased cold-stimulated BAT activity and browning of subcutaneous WAT compared with lean sedentary males. Subjects/methods: Twelve endurance-trained athletes and 12 lean sedentary males were measured during 2 h of mild cold exposure to determine cold-induced BAT activity via [ 18 F]fluorodeoxyglucose-positron emission tomography-computed tomography ([ 18 F]FDG-PET-CT) scanning. Skeletal muscle FNDC5 expression, as well as plasma irisin and IL-6 levels were determined. In addition, a subcutaneous abdominal WAT biopsy was taken to measure gene expression of several markers for browning of WAT. Results: Cold-induced BAT activity was significantly lower in athletes, and no differences in gene expression of classical brown and beige adipocyte markers were detected in subcutaneous WAT between the groups. As expected, mRNA expression of FNDC5 in skeletal muscle was significantly higher in endurance athletes but plasma irisin and Il-6 levels were similar in both groups. Conclusions: These results indicate that chronic endurance exercise is not associated with brown and beige adipocyte recruitment; in fact endurance training appears to be linked to lower the metabolic activity of BAT in humans.